2020
DOI: 10.1016/j.fishres.2020.105532
|View full text |Cite
|
Sign up to set email alerts
|

Diversification, efficiency and productivity in catch share fisheries

Abstract: Fishermen's livelihood face high income variability driven by a combination of biological/ecological, economic, good/bad fortunte, management, and climatic factors. As with other extractive industries such as agriculture, fishermen may resort to diversification as a means to reduce revenue variability by spreading their fishing activity across fisheries and/or fishing grounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This relates to the perceived ignorance of the state with respect to the multi-species nature (and history) of small-scale fishing: that in reality, fishers catch whatever they can find. Thus, the basis of the fishers’ complaint is that the state removed a right they had in the past, and made it difficult for them to develop one of the most common strategies to cope with risks: diversification of catches (Solís and del Corral 2020 ; Robinson et al 2020 ). Conversely, state officials couch their justifications in terms of sustainability discourses, arguing that regulation is needed to avoid overexploitation; in turn, they contend that need for restrictions is misinterpreted as the need to formalize artisanal and small-scale fishers.…”
Section: Resultsmentioning
confidence: 99%
“…This relates to the perceived ignorance of the state with respect to the multi-species nature (and history) of small-scale fishing: that in reality, fishers catch whatever they can find. Thus, the basis of the fishers’ complaint is that the state removed a right they had in the past, and made it difficult for them to develop one of the most common strategies to cope with risks: diversification of catches (Solís and del Corral 2020 ; Robinson et al 2020 ). Conversely, state officials couch their justifications in terms of sustainability discourses, arguing that regulation is needed to avoid overexploitation; in turn, they contend that need for restrictions is misinterpreted as the need to formalize artisanal and small-scale fishers.…”
Section: Resultsmentioning
confidence: 99%
“…Future research could re‐examine the optimal design of IFQ rules and management policies in the context of complex fisheries and explore ways to unlock efficiency gains, such as from diversification in production (Solís et al . 2020), for instance by reducing the wasteful discards of bycatch. Such additional gains in efficiency could, in turn, lead to further adjustments of fleet sizes to optimal levels.…”
Section: Discussionmentioning
confidence: 99%
“…ITQ systems have driven efficiency and investment in fisheries but issues concerning the balance between the economic performance and the wider community have continued to surface (Chu, 2009;Eythórsson, 2000;McCay et al, 1995;Young et al, 2018). Concerns regarding controlling the market power in an ITQ system to prevent monopolies or excessive shares, ensuring co-management of the resource and understanding the impact of increased efficiency on the wider community are common across ITQ implementations globally and the experience of these stakeholders aligns with this (Anderson, 2008;Arnason, 2005;Chu, 2009;Kasperski & Holland, 2013;Solís et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In North America a variety of studies of ITQ systems across species and regions report similar themes. These show consolidation in the West Coast and Alaskan catch share fisheries in the USA's EEZ (Kasperski & Holland, 2013) and concentration of ownership leading to increases in the cost of catch shares in the US Gulf of Mexico red snapper fishery (Solís et al, 2020). An analysis by Chu (2009) of 20 stocks managed by ITQ across Australia, North America, The Netherlands, Iceland, Chile and New Zealand showed that ITQs alone did not aid in the maintenance of stocks at appropriate levels (only 12 of the 20 stocks experienced improvements) as other factors, especially the setting of an appropriate TAC, had an impact on performance.…”
Section: Discussionmentioning
confidence: 99%